Comparison of oxytocin, methylergometrine and carboprost as uterotonics in the active management of third stage of labour - Lamba, A.; Joshi, G.; C. Purohit, R. (Scientific Journal of Medical Science, 2014)
To compare the efficacy of 10 units oxytocin, 0.2 mg methylergometrine and 250 microgram carboprost in the active management of third stage of labour. A randomized comparative study enrolling 300 women was donein the Department of Obstetrics and Gynecology of Dr. Susheela Tiwari Government Hospital, Haldwani. They were randomly allotted into one of the groups.Active management of third stage of labour was done using one of the three uterotonics as per the group of the patient.The main outcome measures were the amount of blood loss, the duration of third stage of labour, drop in hemoglobin and hematocrit levels, need for additional oxytocics and side effects of the drugs.Statistical analysis was done with ANOVA. The three groups were comparable with regard to age and parity.Carboprost was associated with least amount of blood loss (p = 0.01) and least duration of third stage of labour (p = 0.02) amongst the three groups. There was no significant difference in the fall in hemoglobin and hematocrit concentration. Need for additional oxytocics was highest in methylergometrine group (5%).Methylergometrine and carboprost were associated with a number of unpleasant side effects as compared to oxytocin.However all the side effects were acceptable and preferable to the excessive blood loss. Thus it is concluded that carboprost shortened the third stage of labour, minimised bleeding and safeguarded against postpartum hemorrhage effectively as compared to oxytocin and methylergometrine but it is expensive and associated with a number of unpleasant side effects.